Rapid necrosis II: physiological and molecular analysis of 2, 4-D resistance in Sumatran fleabane (Conyza sumatrensis). Issue 1 (28th January 2022) - de Queiroz, Andrew R. S.; Delatorre, Carla A.; Markus, Catarine; Lucio, Felipe R.; Angonese, Paula S.; Merotto, Aldo
Abstract: In 2015, plants of Sumatran fleabane [ Conyza sumatrensis (Retz.) E. Walker] were identified in a crop field with an unusual rapid necrosis herbicide symptom after application of 2, 4-D. An initial study identified that the symptoms began about 2 h after herbicide application, the resistance factor was high (resistance factor = 19), and the resistance decreased at low light. The mechanism of resistance is not yet known, but the symptomatology suggests it may be related to reduced translocation, ATP-binding cassette (ABC) class B transporters, changes on auxin perception genes, or induction of genes involved in response to pathogens and abiotic stresses. The objective of this study was to use inhibitors of enzymes involved in detoxification and carriers to investigate the mechanisms involved in the resistance to 2, 4-D caused by rapid necrosis. Neither the inhibitors of ABC and auxin transporters, triiodobenzoic acid (TIBA), 1-N-naphythylphthalamic acid (NPA), verapamil, and orthovanadate, nor the inhibitors of detoxifying enzymes, such as malathion, 4-chloro-7-nitrobenzofurazan (NBD-Cl), and imidazole, reduced the frequency of the rapid necrosis phenotype. However, orthovanadate and sodium azide (possibly related to auxin transport) were able to partially reduce oxidative stress in leaf disks. The expression of ABCM10 (an ABCD transporter gene), TIR1_1 (an auxin receptor gene), and CAT4 (an amino acid transporter gene) was quickly reduced after 2, 4-D application in the resistant accession. Contrary to our hypothesis, LESION SIMULATING DISEASE RESISTANCE 1_3 ( LSD1_3 ) expression increased in response to 2, 4-D. LSD1_3 is important for the response to pathogen and abiotic stresses. The rapid necrosis mechanism is not related to 2, 4-D detoxification but might be related to changes in the TIR receptor or auxin transport. Mutations in other transporters or in proteins involved in abiotic and pathogen stresses cannot be ruled out.